Genre-sensitive neural situation entity classifier (DE, EN) - Becker, Maria (Universität, 2019)
This is a Classifier for situation entity types as described in Becker et al., 2017. These clause types depend on a combination of syntactic-semant...
Kind of data: Program source code, python scripts
Gesehen am 24.10.2019
Keywords: Forschungsdaten; Datenbank